Physical activity level as a predictor of healthy and chronic disease-free life expectancy between ages 50 and 75. (15th March 2018) - Leskinen, Tuija; Stenholm, Sari; Aalto, Ville; Head, Jenny; Kivimäki, Mika; Vahtera, Jussi
Abstract: Background: physical activity promotes healthy aging. However, little is known about the relationship between physical activity levels and healthy and chronic disease-free life expectancy (LE). The study aim was to examine healthy and chronic disease-free LE between ages 50 and 75 and across various levels of physical activity by sex and different occupational statuses. Methods: overall, 34, 379 women (mean age 53.2 (SD 2.9) years) and 8, 381 men (53.6 (SD 3.2) years) from the Finnish Public Sector study were categorized into five physical activity levels (inactive to vigorously active) according to self-reported physical activity and into three occupational statuses at the first observation point. Partial LE between ages 50 and 75 based on discrete-time multistate life table models was defined using two health indicators: healthy LE based on self-rated health and chronic disease-free LE based on chronic diseases. The average follow-up time for health indicators was 6.8 (SD 5.2) years. Results: a clear dose–response relationship between higher physical activity levels and increased healthy and chronic disease-free LE in men and women, and within occupational statuses was found. On average, vigorously active men and women lived 6.3 years longer in good health and 2.9 years longer without chronic diseases between ages 50 and 75 compared to inactive individuals. The difference in years in good health between vigorously active and inactive individuals was the largest in individuals with low occupation status (6.7 years). Conclusion: higher levels of physical activity increase healthy and chronic disease-free years similarly in men and women, but more among persons with low than with high occupational status.